THE LIFE AND SCIENTIFIC HERITAGE OF SA'UDUDDIN TAFTAZANI - Bo‘tayev Sardor Choriyevich (Web of Journals Publishing, 2023)
Taftazani's scientific legacy belongs to the school of ancient Greek philosophers and logicians, who took a worthy place in the history of social and political thinking of the peoples of the Near and Middle East. But it is noteworthy that it was developed and enriched with new ideas from the height of the Eastern Renaissance, not limited to scientific achievements before our era. Taftazani worked effectively in the scientific environment of Samarkand during the time of Timur together with the scientists of that time, and later became world famous. He remained in history as one of the thinkers who prepared the ground for the creation of the Ulugbek school. He applied logical conclusions to the Islamic philosophy of kalam, strengthened it and made a great contribution to the development of theology as an attractive science. The scientific value of his works has not lost its power even now. Studying the scientific heritage of Taftazani allows us to enrich the golden pages of the history of our thought.
Keywords: Taftazani